Use of Vaccines in Finfish Aquaculture - Roy P. Yanong (EDIS)
FA156, an 8-page fact sheet by Roy P. E. Yanong, uses a question-and-answer format to address the topic of vaccine use in warm water aquaculture facilities. Includes references. Published by the UF Program in Fisheries and Aquatic Sciences, School of Forest Resources and Conservation, December 2008.